«Vamos sazonando poco a poco» ‘Go’-constructions in Spanish spoken in Cuba and Mexico (Islas, 2023)
Introduction: Cooking videos and video blogs are a popular format of broad divulgation. From a linguistic point of view, they constitute a highly instructive type of discourse characterized by particular linguistic structures. In this context, some periphrastic constructions based on the motion verb ir ‘go’ (ir a + INF, ir + gerund and the periphrastic chain ir a + ir + gerund), whose semantic-functional analysis is the focus of this article, are of particular interest.Methods: After summarizing the semantic values of the go-constructions, a brief summary of the works devoted to its use in Spanish spoken in Cuba and Mexico will be given. The empirical part consists of the quantitative and qualitative analysis of a microcorpus, orthographically transcribed, of approximately 130 minutes of culinary discourses from Cuban and Mexican cooking programs.Results: The study shows that the use of the constructions in the analyzed context, in general terms, corresponds to the well-known functions. However, it must be noted that the semantic values of ir a + INF, ir + ger. and their combinations are not limited to the aspectual and temporal use. Rather, what dominates the central part of the discourse is a pragmatic-textual value.Conclusions: Beyond the detailed analysis, the discussion of the topic reveals that the description of grammatical phenomena is still strongly influenced by well-established categories and Eurocentric views that are seldom questioned.
Keywords: motion verbs; verbal periphrases; grammaticalization; Mexican Spanish; Cuban Spanish